Competitive Balance in the Austrain, Czech, Hungarian and Ukranian Soccer Leagues - Jan Šíma; Jan Procházka (Karolinum Press, 2015)
Competitive Balance in the Austrain, Czech, Hungarian and Ukranian Soccer Leagues This study deals with measuring and evaluating the static competitive balance in four chosen national soccer/football leagues. These are (in alphabetical order) the premier leagues in the Austrian, Czech, Hungarian, and Ukrainian soccer/football divisions. Static balance shows how teams in the league tables of each year differ from each another. It is determined by a calculation of determinant divergences in the percentages of winnings. The results of this work provide graphic illustrations of the development of the competitive balance in the aforementioned contests over the latest forty-two years. They identify the development trend of this phenomenon. Of the contests studied, it is the Czech premier league which used to show the highest static balance. However, nowadays, the Austrian and Hungarian leagues are more balanced in the short term. On the contrary, it is the Ukrainian league which is the least balanced. There is an apparent longterm decline of competition balance within all of the analyzed competitions. However, this decline varies a lot within the group. Vyrovnanost soutěže v rakouské, české, maďarské a ukrajinské fotbalové lize Studie se zabývá měřením a vyhodnocením statické vyrovnanosti soutěže čtyř vybraných národních fotbalových lig. Těmito ligami (alfabeticky řazeno) jsou česká, maďarská, rakouská a ukrajinská liga. Statická vyrovnanost vypovídá o tom, jak se od sebe lišily týmy v ligových tabulkách každého ročníku. Je stanovena pomocí výpočtu směrodatných odchylek v procentech výher. Výsledky této práce ukazují za pomoci grafů vývoj statické vyrovnanosti vybraných soutěží za posledních čtyřicet dva let. Určují vývojový trend tohoto fenoménu. Z vybraných soutěží vykazuje česká liga nejvyšší statickou vyrovnanost. Přesto jsou dnes rakouská a maďarská liga krátkodobě vyrovnanějšími. Naopak ukrajinská liga je nejméně vyrovnaná. U všech studovaných soutěží lze zaznamenat viditelný pokles vyrovnanosti soutěže. Tento trend se však ve skupině liší.